EXPLORING CAREER CRYSTALLIZATION AMONG INDONESIAN STUDENT IN MALAYSIA - Sururi, Ahmad (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
Industry Revolution 4.0 is acquiring numerous progressions to the world and one of the transformations is on the future workplace. Hence, students will be largely affected and have a big responsibility to adapt and survive the changes. As mentioned in Super?s theory, students must have some abilities during a certain period. And in light of Super?s career life span theory, students have to achieve their career crystallization. Ironically many students, be that as it may, did not meet the ability on crystallization sub-stage. That is the reason a large number of students getting jumbled between their education background and career later on. This study aimed to investigate vocation crystallization Indonesian students in Malaysia. The case study was used which involved a semi-structured interview and the participant is a student who is studying at the University of Malaya. This investigation indicated that during crystallization sub-stage there are three significant things which are crystallization conduct, resources career information, and determining career choice. Alongside students themselves, schools and counsellors are required to assume a key role in guaranteeing this to happen.